Persistent effects of playing football and associated (subconcussive) head trauma on brain structure and function: a systematic review of the literature. Issue 22 (4th November 2016) - Tarnutzer, A A; Straumann, D; Brugger, P; Feddermann-Demont, N
Abstract : Aim/objective: There is ongoing controversy about persistent neurological deficits in active and former football (soccer) players. We reviewed the literature for associations between football activities (including heading/head injuries) and decline in brain structure/function. Design: Systematic literature review. Data sources: MEDLINE, Embase, PsycINFO, CINAHL, Cochrane-CRCT, SportDiscus, Cochrane-DSR=4 (accessed 2 August 2016). Eligibility criteria for selecting studies: Original studies reporting on football-related persistent effects on brain structure/function. Results from neurocognitive testing, neuroimaging and EEG were compared with controls and/or correlated with heading frequency and/or head injuries. Methodological quality was rated for risk-of-bias, including appropriateness of controls, correction for multiple statistical testing and assessment of heading frequency and head injuries. Results: 30 studies with 1691 players were included. Those 57% (8/14) of case–control studies reporting persistent neurocognitive impairment had higher odds for inappropriate control of type 1 errors (OR=17.35 (95% CI (10.61 to 28.36)) and for inappropriate selection of controls (OR=1.72 (1.22 to 2.43)) than studies observing no impairment. Studies reporting a correlation between heading frequency and neurocognitive deficits (6/17) had lower quality of heading assessment (OR=14.20 (9.01 to 22.39)) than studies reporting no such correlation. In 7 of 13 studies (54%), the number of head injuries correlated with the degree of neurocognitive impairment. Abnormalities on neuroimaging (6/8 studies) were associated with subclinical neurocognitive deficits in 3 of 4 studies. Summary/conclusions: Various methodological shortcomings limit the evidence for persistent effects of football play on brain structure/function. Sources of bias include low-quality assessment of heading frequency, inappropriate control for type 1 errors and inappropriate selection of controls. Combining neuroimaging techniques with neurocognitive testing in prospective studies seems most promising to further clarify on the impact of football on the brain.